Analyzing stance in online threat discourse by anti-immigration attackers: an integrated approach - Mustafa, Marwa (AUC Knowledge Fountain, 2020)
The present study examines the construct of stance in two subsequent threat manifestos recently published by anti-immigrant attackers in the year 2019. The first one, The Great Replacement, was published online by Brenton Tarrant before shooting and “murdering 51 people in two mosques in Christchurch, New Zealand” (Roy, 2020) in March 2019. The second manifesto, The Inconvenient Truth, was published online as well by Patrick Crusius before “killing 22 people and injuring dozens of others at an El Paso Walmart” in Texas, USA (Moore & Berman, 2020) in August 2019. For this purpose, a ‘synergy’ of critical discourse analysis (CDA) and methods of corpus linguistics (CL) approaches (Baker et al., 2008) is used to reveal the ideologies of those attackers as well as the established relationship between language, power and ideology in their discourses. The results of this CDA-CL integrated approach show a consistent positive evaluation act of the attackers themselves and their in-groups against a negative evaluation act of the targeted groups in both manifestos. The methodological synergy used herein shows some common discursive and linguistic strategies in both threat discourses with further implications referring to the role of the deeply rooted xenophobic ideology that could eventually lead its followers to act against foreigners in general either by using a racist discourse or through violent acts, or both as exemplified in the discourses analyzed herein.